The Effect of Goodwill Accounting Treatment and Investment Knowledge on Investment Interest in The Capital Market (Case Study of Accounting Department Students of UNPAB) - Tesalonika Tampubolon; Kristin Natalia Doloksaribu; Triya Vebrianty; M Syukrillah Putra; Rifka Sari Br Surbakti; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
In the capital market at Panca Budi University (UNPAB), this study aims to investigate how goodwill accounting methods and investing knowledge affect students' willingness in making investments. 100 respondents were given questionnaires to complete in order to collect data for this study, which used quantitative research methodologies and random sampling. Multiple linear regression was used to analyze the data and assess the hypotheses that were put forth. Students' interest in capital market investments is positively and significantly impacted by both goodwill accounting practices and investing knowledge, according to the research. For educational institutions and capital market experts looking to improve students' investing literacy, these findings provide insightful information.